Philosophy and Human Nature - Muslim Muslim (Indonesian Journal for Islamic Studies, 2023)
This research is to find out what philosophy is, to find out the philosophical views of human nature, to find out the relationship between human nature and philosophy. Philosophical thinking is knowledge, this is about knowledge starting with curiosity, certainty starting with doubt and philosophy starting with both of them. Science is a part of knowledge that is learned to be able to know everything in life. Often a person has a desire to know something. Something you want to know exists in everyday life. There are times, curiosity is just curiosity that A moment. Human nature is a servant and caliph of Allah on earth which consists of three elements, namely physical, intellectual and spiritual. This humans as servant and caliph of Allah on earth, then humans are God's creatures, creatures created in a helpless condition, needing help from other beings who have the ability to think, creatures who have reason, creatures who are always curious about everything, creatures who have the ability to speak, creatures who are able to make tools for social beings who are able to work together, creatures that are able to organize excrement to meet their needs, creatures that live on the basis of economic principles, creatures that are religious, rational beings who are free to act based on moral reasons, creatures with a social contract to respect and protect rights other people The link between human nature and philosophy also provides an understanding or awareness to humans of the meaning of knowledge about reality provided by philosophy.